2013
DOI: 10.1093/jac/dkt257
|View full text |Cite
|
Sign up to set email alerts
|

Community-associated Clostridium difficile infection among older people in Tayside, Scotland, is associated with antibiotic exposure and care home residence: cohort study with nested case-control

Abstract: Objectives: To estimate the risks of community-associated Clostridium difficile infection (CA-CDI) among the population aged ≥65 years associated with antibiotic exposure and care home residence. Population and methods:We linked cases from a prospective study in Tayside, Scotland from 1 November 2008 to 31 October 2009 to population datasets to conduct a cohort study and a nested, matched (1 : 10 by age and gender) case-control study.Results: There were 79039 eligible residents. CA-CDI incidence was 20.3/10 00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…National result showed that the prevalence of antimicrobial use was lower than the prevalence of infections, thus the overuse of antimicrobials is not common in participating LTCFs. Although prescription of quinolone antibacterials was frequent (34.2%) in LTCFs, which can lead the increased presence of infections caused by Clostridium diffi cile and other antimicrobial resistant pathogens [22][23][24][25][26][27]. This result is similar to several overseas studies that quinolones are the most frequently prescribed antibacterials in LTCFs [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…National result showed that the prevalence of antimicrobial use was lower than the prevalence of infections, thus the overuse of antimicrobials is not common in participating LTCFs. Although prescription of quinolone antibacterials was frequent (34.2%) in LTCFs, which can lead the increased presence of infections caused by Clostridium diffi cile and other antimicrobial resistant pathogens [22][23][24][25][26][27]. This result is similar to several overseas studies that quinolones are the most frequently prescribed antibacterials in LTCFs [20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…Clindamycin was initially associated with CDI, but more recently, fluoroquinolones, widely used in IBD patients, have become the most common risk factor for CDI (4). The mechanism through which the use of antibiotics leads to increased risk for CDI development is the disruption of normal intestinal flora and the subsequent proliferation of C. difficile.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Illustratively, in USA alone, hospital discharges with CDI as the main diagnosis registered a 237% increase from 2000 to 2009, and accounted for hospital mortality rate similar to that of gastrointestinal bleeding (2), with healthcare costs estimated between 1.2 and 3 billion US dollars each year (3). In addition to broad-spectrum antimicrobial therapy, which is the most widely recognized causative factor for CDI (4), other potential risk factors, such as advanced age, prolonged hospitalization, chemotherapy, immunosuppression, multiple co-morbidities, hypoalbuminemia, renal insufficiency, use of proton pump inhibitors, and the emergence of a hypervirulent strain of the bacterium known as NAP1 (North American pulsed field type1) in some North-American and European areas, have been identified to explain the increased incidence of CDI (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a cohort study of community-associated CDI infection among older people and the relationship between infection, antibiotic exposure, and care home residence, authors reported an increased mortality among subjects that whose infections were healthcare-onset, but not among CDI cases in the community [2]. Similarly, in the study of Garg et al [15], the highest mortality was found among C. difficile infection cases in hospital (9.4%) while the percentage of deaths was lower in long-term care facility CDI cases (7.6%) and in community acquired infections (2.3%).…”
Section: Mortality Associated With C Difficile Among Elderly and Nurmentioning
confidence: 99%